О некоторых примерах вариативности современного английского языка в США - Герасимюк, Е.И.; Исаев, Э.Ш. (Культура народов Причерноморья, 2014)
Статья посвящена актуальной на сегодняшний день проблеме в социолингвистике -
изучению языковой вариативности английского языка в США. Целью данной статьи является
рассмотрение языковой вариативности английского языка на примере употребления молодежного
сленга в разных сферах общественной жизни. На основе проанализированного материала предпринята
попытка дать оценку современной языковой ситуации в США. Для решения задач применяются
следующие методы социолингвистического исследования: индуктивно-дедуктивный метод, метод
лексического отбора, метод сопоставительного анализа и описательный метод. Стаття присвячена актуальній на сьогоднішній день проблемі у соціолінгвістиці - вивченню
мовної варіативності англійської мови в США. Метою даної статті є розгляд варіативності
англійської мови на прикладі вживання молодіжного сленгу в різних сферах суспільного життя. На
основі проаналізованого матеріалу зроблено спробу дати оцінку сучасної мовної ситуації в США. Для
вирішення завдань застосовуються такі методи соціолінгвістичного дослідження: індуктивно-
дедуктивний метод, метод лексичного відбору, метод порівняльного аналізу та описовий метод. The article is devoted to a significant problem in sociolinguistics - the studying of the language
variability of English in the USA. The purpose of this article is to examine the variability of English language on
example of using the youth slang in different spheres of public life. On the basic of the analyzed material was
made an attempt to estimate a current linguistic situation in USA. Despite the conventional importance, the
analysis of linguistic sources testifies that the phenomenon of variability of modern English still wasn't
fundamentally investigated. Consequently, scientific novelty of this research is, that in it for the first time
reflected English speakers attitude to such concepts as: "language norm" and "youth slang". To solve the
problems, the following methods of linguistic research have been used: the inductive-deductive method, which
allows to understand and summarize the relevant theoretical and practical material. The lexicographic method
of selection, helped select lexicographical sources, press materials, scientific publications, monographs, which
were needed during sociolinguistic analysis. The method of the comparative analysis was used in the analysis of
linguistic variants to identify differences in their use. The descriptive method was necessary for establishment of
specifics of realization of linguistics variation within the country.